BEST PROXIMITY POINTS INVOLVING SIMULATION FUNCTIONS WITH $(τ)$-DISTANCE - Arunchai, A.; Suppalap, S.; Tapanyo, W. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
In this paper, we generalize some the best proximity point results in metric space involving simulation functions with เธฃยเนโฌย-distance, given by เธฃยเนโฌย-distance is lower semicontinuous in its first variable. Inspired by using the concept of w0-distance which is a special case of w-distance. As a consequence, several best proximity point theorems are obtained.